A theoretical exploration of the effect and mechanism of CO on NO2 heterogeneous reduction over carbonaceous surfaces. (15th April 2021) - Yue, Shuang; Wang, Chunbo; Xu, Ziyang; Zheng, Fei; Si, Tong; Anthony, Edward J.
Highlights: Four channels of NO2 heterogeneous reduction reaction were proposed by DFT calculation. A thorough exploration for the effect mechanism of CO was performed by systematic analyses. The introduction of CO has the different influence on the stages of NO2 reduction and CO2 desorption. The adsorption mode of CO shows a greater effect on CO2 desorption than NO2 reduction. Abstract: A thorough understanding of the NO2 heterogeneous reduction reaction over a carbonaceous surfaces can help with the goal of providing useful information to aid in controlling NOx emissions. Multiple adsorption structures and reaction pathways on zigzag surfaces were obtained via density functional theory (DFT) calculation, revealing the effect and mechanism of the CO presence and its adsorption mode. Calculation results showed that the introduction of CO at the stage of CO/CO2 desorption accelerates the dissociation of CO2 from a zigzag surface. According to the theory of frontier molecular orbital, the CO presence promotes the transfer of electrons from the char surface to the CO2 moiety, decreasing the energy barrier of CO2 desorption. On the other hand, kinetic and thermodynamic analysis indicates that the introduction of CO during NO2 reduction facilitates the reduction of NO2 to NO, but has little influence on the reduction rate. In addition, the adsorption mode of CO shows little effect on the weak interaction between NO2 moiety and the char edge, but has a significant effect on the weak interaction between CO moiety and char edge. Thus, as the adsorption mode of CO changes, a significant difference in mechanisms can be observed at the stage of CO2 desorption rather than NO2 reduction. To sum up, these theoretical results reveal in detail the effect and mechanism of CO on NO2 heterogeneous reduction, which further explain previous experimental results.